Multiple CAR-T cell therapy for acute B-cell lymphoblastic leukemia after hematopoietic stem cell transplantation: A case report - Deng, Lei; Xiaolin, Yu; Wu, Qian; Song, Xiaochen; Li, Wenjun; Hou, Yixi; Liu, Yue; Wang, Jing; Tian, Jun; Zuo, Xiaona; Zhou, Fang (Frontiers in Immunology, 2022)
B-cell acute lymphoblastic leukemia (B-ALL) is the most common childhood malignancy. The cure rate has reached 90% after conventional chemotherapy and hematopoietic stem cell transplantation (HSCT), but the prognosis of patients with relapsed and refractory (R/R) leukemia is still poor after conventional treatment. Since FDA approved CD19 CAR-T cell (Kymriah) for the treatment of R/R B-ALL, increasing studies have been conducted on CAR-T cells for R/R ALL. Herein, we report the treatment of a patient with ALL who relapsed after allogeneic HSCT, had a complete remission (CR) to murine scFv CD19 CAR-T but relapsed 15 months later. Partial response was achieved after humanized CD19 CAR-T treatment, and the patient finally achieved disease-free survival after sequential CD22 CAR-T treatment. By comparing the treatment results of different CAR-T cells in the same patient, this case suggests that multiple CAR-T therapies are effective and safe in intramedullary and extramedullary recurrence in the same patient, and the expansion of CAR-T cells and the release of inflammatory cytokines are positively correlated with their efficacy. However, further clinical studies with large sample sizes are still needed for further clarification.